Investigation of antioxidant and anticonvulsant activity of Hypericum triquetrifolium Turra - ÇAM, MUHAMMET EMİN; TAŞKIN, TURGUT (My University, 2022)
© 2022 Marmara University Press.Epilepsy is a state characterized by sudden, recurrent epileptic seizures that are not initiated by an identifiable event. There are various studies has been shown that Hypericum species may be used for their anticonvulsant potentials. Besides, the relationship between anticonvulsant activity and antioxidant effect has already been shown in the literature. In the current study, H. triquetrifolium was investigated for the first time for its potential antioxidant and anticonvulsant potential using in vitro and in vivo test models. H. triquetrifolium extracts were tested with DPPH assay, FRAP assay, copper (II) ion reducing antioxidant capacity assay, and acetylcholinesterase inhibitory activity assay to understand their antioxidant potential. Especially, methanolic extract of H. triquetrifolium was shown the highest antioxidant activity. Moreover, a pentylenetetrazole (PTZ, 80 mg/kg, i.p.)-induced seizure model was conducted to analyze the anticonvulsant activities of H. triquetrifolium extracts in mice. In addition, this study revealed that H. triquetrifolium decreased the ratio of severe seizures and increased the mean onsite of mortality and survival rate in a dose-dependent manner. It is thought that the anticonvulsant effect may be either related to the antioxidant potential of H. triquetrifolium or its interference in the GABAergic system.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); anticonvulsant activity; antioxidant activity; epilepsy; Hypericaceae; Hypericum triquetrifolium Turra